Early correction of malocclusion using planas direct tracks - Santos, Renata Reis dos [UNESP]; Garbin, Artênio José Isper [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (Hindawi Publishing Corporation, 2013)
The correction of functional posterior crossbite through Planas Direct Tracks has many characteristics that can become advantages. The aim of this study was to present a clinical case showing how to use this procedure for early correction with resources available through public health services. The patient, a 4-year-old girl, arrived to receive treatment due to a functional unilateral crossbite. When the mandible was moved to the centric position, it was observed that the teeth had occlusal trauma. An occlusal adjustment was performed. The adjustment was not sufficient to promote functional equilibrium; thus, Planas Direct Tracks were made, resulting in functional equilibrium and correction of the malocclusion. As shown in the case report, the Planas Direct Tracks were effective for the correction of the posterior crossbite. If malocclusion is considered a public health problem, implementation of low-cost and easy-to-execute techniques is needed.